Energy reconstruction of hadronic showers at the CERN PS and SPS using the Semi-Digital Hadronic Calorimeter. (1st July 2022) - Boumediene, D.; Pingault, A.; Tytgat, M.; W. Baek, Y.; Kim, D-W.; Lee, S.C.; Min, B.G.; Park, S.W.; Deguchi, Y.; Kawagoe, K.; Miura, Y.; Mori, R.; et al.
Abstract: The CALICE Semi-Digital Hadronic CALorimeter (SDHCAL) is the first technological prototype in a family of high-granularity calorimeters developed by the CALICE Collaboration to equip the experiments of future lepton colliders. The SDHCAL is a sampling calorimeter using stainless steel for absorber and Glass Resistive Plate Chambers (GRPC) as a sensitive medium. The GRPC are read out by 1 cm× 1 cm pickup pads combined to a multi-electronics. The prototype was exposed to hadron beams in both the CERN PS and the SPS beamlines in 2015 allowing the test of the SDHCAL in a large energy range from 3 GeV to 80 GeV. After introducing the method used to select the hadrons of our data and reject the muon and electron contamination, we present the energy reconstruction approach that we apply to the data collected from both beamlines and we discuss the response linearity and the energy resolution of the SDHCAL. The results obtained in the two beamlines confirm the excellent SDHCAL performance observed with the data collected with the same prototype in the SPS beamline in 2012. They also show the stability of the SDHCAL in different beam conditions and different time periods.